Root Canal Preparation and Enlargement Using Thermally Treated Nickel-Titanium Rotary Systems in Curved Canals - Barreto Pivoto-Joao, Mariana Mena [UNESP]; Tanomaru-Filho, Mario [UNESP]; Pinto, Jader Camilo [UNESP]; Espir, Camila Galletti [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Elsevier B.V., 2020)
Introduction: The purpose of this study was to evaluate root canal preparation and apical enlargement of curved canals using rotary heat-treated and heat/surface-treated systems by micro computed tomographic imaging. Methods: Curved mesial root canals (n = 48) of mandibular molars (20 degrees-40 degrees) were prepared using ProDesign Logic (PDL; Easy Equipamentos Odontologicos, Belo Horizonte, MG, Brazil) 25/.01 and 25/.06 or HyFlex EDM (HFEDM) 10/.05, HyFlex CM 20/.04, and HFEDM 25/.08. Apical enlargement was performed using PDL 40/.05 or HFEDM 40/.04. Scanning (9 lim) was performed before and after preparation and after apical enlargement using micro computed tomographic imaging. Volume, percentage of volume increase, debris, untouched root canal surface, and centering ability were analyzed. Statistical analysis was performed using Mann-Whitney, Wilcoxon, and unpaired t tests (alpha = .05). Results: HFEDM promoted a higher volume increase of the root canals than PDL after preparation and after apical enlargement (P < .05). The apical enlargement promoted a significant decrease in debris and untouched surface in both groups (P < .05). The percentage of debris and untouched surface were similar between HFEDM and PDL after preparation and after apical enlargement (P > .05). Both systems promoted centered canals (P > .05). Conclusions: HFEDM instruments promoted greater volume of the root canal than PDL. However, the cleaning ability of the instruments was similar. The apical increase up to size 40 with both instruments provided less debris and untouched surfaces and allowed centralization of the curved root canals.
Keywords: Endodontic treatment; micro-computed tomography; nickel-titanium endodontic instruments; root canal preparation